2022
DOI: 10.1159/000524048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex on Outcomes of Mechanical Thrombectomy in Basilar Artery Occlusion: A Multicentre Cohort Study

Abstract: <b><i>Introduction:</i></b> Identifying differences in outcome of basilar artery occlusion (BAO) between males and females may be useful in aiding clinical management. Recent studies have demonstrated widespread underrepresentation of women in acute stroke clinical trials. This international multicentre study aimed to determine sex differences in outcome after mechanical thrombectomy (MT) for patients with acute BAO. <b><i>Methods:</i></b> We performed a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
2
2
Order By: Relevance
“…Our findings also showed that young female cohorts have high collateral grades (64.52% vs. 59.50%), but the difference between men and women was insignificant. In addition, lower rates of bridge intravenous thrombolysis (19.07% vs. 39.40%), hypertension (59.21% vs. 76.20%), and diabetes (19.07% vs. 28.8%), and shorter onset to puncture time (330 vs. 359.60 mins) were found in young patient in our study compared with a multicenter cohort study [34]. The findings of Guenego et al supported our results as sex was a predictor of mortality in patients with BAO treated with EVT [37].…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Our findings also showed that young female cohorts have high collateral grades (64.52% vs. 59.50%), but the difference between men and women was insignificant. In addition, lower rates of bridge intravenous thrombolysis (19.07% vs. 39.40%), hypertension (59.21% vs. 76.20%), and diabetes (19.07% vs. 28.8%), and shorter onset to puncture time (330 vs. 359.60 mins) were found in young patient in our study compared with a multicenter cohort study [34]. The findings of Guenego et al supported our results as sex was a predictor of mortality in patients with BAO treated with EVT [37].…”
Section: Discussioncontrasting
confidence: 44%
“…Chalos et al [33] also demonstrated that sex could not predict mortality within 90 days in patients who underwent EVT. Among patients with BAO, Tan et al [34] indicated that the functional outcomes were comparable between men and women. One cause of the discrepancy between ours and the aforementioned studies may be the included population.…”
Section: Discussionmentioning
confidence: 99%
“…28 A recent study of the effect of sex on the outcome of mechanical thrombectomy in basilar artery occlusion (BAO) showed that women achieved comparable functional outcomes compared with men after undergoing mechanical thrombectomy. 29 However, this is not consistent with our findings. This may involve differences in population, economy, medical level, and other aspects.…”
Section: Discussioncontrasting
confidence: 99%
“…4,45 Another interesting result was that the poor outcome group contained a larger number of female patients compared with the favorable outcome group, which agreed with the finding of a prospective cohort study by Madsen et al 46 This is probably attributed to the older age and higher ratio of atrial fibrillation as well as cardioembolic stroke among the female patients. 47,48 More detailed researches are warranted to ascertain the gender difference in endovascular treatment to help formulate the optimal management. Furthermore, elevated NSE might not just be the result of neuronal injury but also involved in pathological process.…”
Section: Discussionmentioning
confidence: 99%